2023
DOI: 10.1101/2023.05.11.540404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibodies Raised Against an Aβ Oligomer Mimic Recognize Pathological Features in Alzheimer’s Disease and Associated Amyloid-Disease Brain Tissue

Abstract: Antibodies that target the β-amyloid peptide (Aβ) and its associated assemblies are important tools in Alzheimer's disease research and have emerged as promising Alzheimer's disease therapies. This paper reports the creation and characterization of a triangular Aβ trimer mimic composed of Aβ17–36 β-hairpins, and the generation and study of polyclonal antibodies raised against the Aβ trimer mimic. The Aβ trimer mimic is covalently stabilized by three disulfide bonds at the corners of the triangular trimer to cr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…RBKLT_20, RBKLT_16, reported the generation and study of polyclonal antibodies raised against an analogue of 2AT that contains the Aβ 24-29 loops. [33] Unlike the 2AT and KLT mAbs reported in the current article, these polyclonal antibodies strongly recognize pathological Aβ in brain slices from individuals who lived with Alzheimer's disease as well as brain slices from 5xFAD mice. These findings taken together with the findings in this article, suggest that the β-hairpin loop may be an important structure for generating antibodies against Aβ oligomer mimics that bind biogenic Aβ assemblies.…”
Section: Immunoreactivity Of the 2at And Klt Mabs With Aβ 42mentioning
confidence: 64%
“…RBKLT_20, RBKLT_16, reported the generation and study of polyclonal antibodies raised against an analogue of 2AT that contains the Aβ 24-29 loops. [33] Unlike the 2AT and KLT mAbs reported in the current article, these polyclonal antibodies strongly recognize pathological Aβ in brain slices from individuals who lived with Alzheimer's disease as well as brain slices from 5xFAD mice. These findings taken together with the findings in this article, suggest that the β-hairpin loop may be an important structure for generating antibodies against Aβ oligomer mimics that bind biogenic Aβ assemblies.…”
Section: Immunoreactivity Of the 2at And Klt Mabs With Aβ 42mentioning
confidence: 64%
“…1,2 Synthetic trimers of peptides derived from Ab have been used to raise antibodies that recognize pathological features in tissues isolated from Alzheimer's brains. 3 Tetramers and octamers of Ab have demonstrated pore-forming activity against lipid-bilayers. 4 Photo-induced crosslinking studies of Ab 42 have revealed the formation of pentamers and hexamers, while ion mobility-mass spectrometry studies have shown that Ab 42 forms b-barrel shaped hexamers in the presence of membrane mimetic micelles.…”
Section: Introductionmentioning
confidence: 99%